Textbook of Bioinformatics - Knight, Regan (United States : States Academic Press, 2022)
Bioinformatics is a field which aims to understand biological data. It is concerned with developing diverse software tools and methods which can facilitate the comprehension of complex biological data. It is an interdisciplinary field that combines concepts and knowledge from the areas of computer science, mathematics, biology, statistics and information engineering. These areas help in an advanced analysis and interpretation of data. The most prominent applications of bioinformatics include identifying the genetic basis of a disease, understanding differences between populations, identification of single nucleotide polymorphisms, understanding protein sequences, identifying candidate genes, understanding the desirable properties amongst agricultural species, etc. This field has contributed in text mining of biological literature for developing gene and biological ontologies. This book provides comprehensive insights into bioinformatics. It elucidates new techniques and their applications in a multidisciplinary manner. This textbook is a complete source of knowledge on the present status of this important field.
Includes index.
Includes bibliographical references.
Keywords: Bioinformatics; Bioengineering; Biochemical genetics; Bioinformatics; Biology -- data processing; Computational biology